PEMETAAN POTENSI KERUSAKAN TANAH DI KABUPATEN POLEWALI MANDAR: Mapping of Potential Soil Damage in Polewali Mandar District - Syamsul Arifin Lias; Syahrul (Universitas Hasanuddin, 2021)
As a natural resources that must be maintained for its sustainability, land with all its functions and roles has an essential position in the ecosystem. As a growing medium for producing biomass, soil has the potential to experience quality degradation due to uncontrolled human activities, especially the production of biomass itself. The first step in overcoming soil damage is to carry out an inventory of the potential soil damage in an area. Inventory can be done by mapping spatially, especially on the potential factors of soil damage. The unavailability of information on potential soil damage, both in terms of area and distribution, is an obstacle in monitoring and controlling soil damage in various areas, including Polewali Mandar District. The purpose of this study was to map the distribution and extent of potential soil damage in Polewali Mandar District. This research was carried out by referring to the technical guidelines for compiling soil damage status maps for biomass production. This map is based on the main thematic maps and other supporting data and information. The potential for soil damage was analyzed using two approaches, namely the superimpose/overlay method or overlapping thematic maps and the scoring method for factors considered to have an effect on soil damage. Based on the results of the weighting analysis of all potential soil damage variables, information is obtained that the research area has 3 classes of potential soil damage. Potential damage II (PR II) with a low class area of ​​49,288.1 Ha or about 23% of the research area. The potential for damage III (PR III) with moderate class is 147,553.7 ha or about 70.7% of the research area. The potential for damage IV (PR IV) with high class area is 613.6 Ha or about 0.3% of the research area.